Exploring the Challenges of Printed Modular Instruction for Learners with Special Needs - Pinote, Mirbeth (Journal of Interdisciplinary Perspectives, 2024)
This study explored the challenges parents and teachers face as a foundation for developing an action plan to enhance printed modular distance learning implementation. This study used a descriptive-comparative research design to compare the challenges teachers and parents encountered during the printed modality implementation. The study sample comprised six teachers and 54 parents, selected through universal sampling. Respondents completed a questionnaire adapted from Abante et al. (2021). Data were analyzed using frequency counts, percentages, weighted means, and independent samples t-tests. The findings revealed that parents experienced significant challenges hiring tutors, while teachers faced substantial difficulties in parent-teacher communication and validating learners’ progress. The statistical analysis indicated no significant difference in the challenges reported by parents and teachers. The study concludes that printed modular distance learning facilitates continuing education at home but falls short of adequately supporting learners with special needs. Consequently, a targeted action plan should be implemented to address these challenges and improve educational outcomes.